Unusual presentation of oxalate nephropathy causing acute kidney injury: A case report - Diab, Anas; Neuman, Michelle M; Diab, Kareem; Gordon, Daniel (Journal of Clinical Nephrology, 2020)
Oxalate nephropathy due to Hyperoxaluria and elevated serum oxalate level is a well-known cause for interstitial fibrosis, and ESRD. Conditions associated with high serum Oxalate, should be considered as a possible contributing factor for a patient’s tubular injury. Well known cause for Hyperoxaluria including enteric Hyperoxaluria (due to gastric bypass, chronic pancreatitis, small Bowel resection, or malabsorption, as well as depletion of enteric oxalate-degrading bacteria [e.g., Oxalobacter). Other known causes of oxalate nephropathy include primary Hyperoxaluria, ethylene glycol intoxication, vitamin B6 deficiency, excessive ingestion of vitamin C or dietary substances rich in oxalic acid, aspergillosis, prolonged renal failure and various drugs (e.g., Known medications to cause Oxalate Nephropathy are: Orlistat, Praxilene, COX-2 inhibitors). Unusual presentation with Acute Kidney Injury with incidental finding of high serum Oxalate in a patient with a known CKD stage III, recently started on Polyethelene Glycol to treat his constipation.